The evaluation of health, disability and aged care-sector engagement with resources designed to support optimisation of the allied health assistant workforce: a qualitative study - Lucy Whelan; Sharon McLean; Alexandra Edwards; Jessica Huglin; Melanie K. Farlie (BMC, 2024)
Abstract Background Allied health assistants (AHAs) support allied health professionals (AHPs) to meet workforce demands in modern healthcare systems. In an Australian context historically, AHAs have been sub-optimally utilised. Prior research has identified that AHAs and AHPs working in health, disability and aged care sectors, and the Vocational Education and Training (VET) industry, may benefit from access to resources to support the optimisation of the AHA workforce. As a part of a Victorian department of health funded project, several resources were developed in line with workforce recommendations for use in each of the above sectors. Recommendations and resources covered the broad areas of pre-employment training, workforce planning and governance, consumer-centred therapy and supports, recruitment and induction and workplace training and development. This study aimed to evaluate the engagement with these newly designed resources to support optimisation of AHAs in the Victorian context. Methods Semi-structured interviews were conducted to evaluate engagement with resources, from the perspective of AHAs, AHPs and allied health leaders (AHLs) in the health, aged care or disability sectors, and educators and managers of allied health assistance training. Thematic analysis was conducted using team-based framework analysis. Results Thematic framework analysis of the interview data identified four themes; Why participants accessed the resources; How participants engaged with the resources; What (if any) changes in practice occurred as a result of engaging with the resources in a participant's local context, How did participants envision the resources being utilised for AHA workforce optimisation in the future. Responses were mapped to the AHA workforce career pathway at the career preparation, career development and career trajectory tiers. Conclusions Appetite for AHA workforce development and optimal utilisation is evident across Victoria, Australia. Readily accessible resources that inform AHA role and scope of practice, delegation practice, or improve the ability for an AHA to state their own development needs, were identified as useful by participants. The potential for these resources to assist in the optimal utilisation and development of AHA workforces across the career continuum differs according to the role, sector and geographical location of the resource user. Further study is needed to investigate the transferability of these resources to national and global contexts.